PENGARUH KECERDASAN INTELEKTUAL DAN KECERDASAN EMOSIONAL TERHADAP HASIL BELAJAR DARI PERSPEKTIF GENDER - Arni Aristiani; Ati Sadiah; Ai Nur Solihat (Jurnal Pendidikan Ekonomi Indonesia, 2021)
The problem in this study is that the learning outcomes of students are quite low. The purpose of this study was to determine the effect of intellectual intelligence and emotional intelligence on student learning outcomes and to determine the differences between intellectual intelligence, emotional intelligence and learning outcomes between male and female students. This study uses a survey method with a quantitative approach, and uses an explanatory research design. The population of this research is class XI SMA Negeri 3 Tasikmalaya for the Academic Year 2020/2021 with 335 students. The sampling technique used was cluster sampling, so 182 samples were obtained. Methods of data collection using a questionnaire and data analysis using Multiple Linear Regression and Independent Sample T Test. The results of the Multiple Linear Regression test, the equation Y`= 36,068 + 0,519 X_1+0,268 X_2 means that intellectual intelligence and emotional intelligence have a positive effect on learning outcomes, from simultaneous testing that intellectual intelligence and emotional intelligence affect visible learning outcomes from the acquisition of F count 208,355 F table 3,046. Then the results of the Independent Sample T Test that there are no differences in intellectual intelligence, emotional intelligence and student learning outcomes between men and women as seen from the t-count value of each variable 0.200, 0.525, 1.893 t table 1.973.